ART OF METALLOGRAPHY: POSSIBILITIES OF DARK-FIELD MICROSCOPY APPLICATION FOR COLORED OBJECTS STRUCTURE ANALYSIS - A. G. Anisovich; I. N. Rumiantsava (Литьë и металлургия, 2015)
The application of the method of dark field microscopy for the study of colored objects of material technology was researched. The capability of corrosive damage analysis and determination of the thickness of the metal coating were demonstrated. The performance capability of analysis of «reflection» in the dark field during the study of non-metallic materials – orthopedic implants and fireclay refractory were tested. An example of defect detection of carbon coating was displayed.